The effect of ethanol extracts of pegagan (Centela asiatica) urban in inhibiting the growth of Staphylococcus aureus and Klebsiella pneumoniae that caused pneumonia - Zinatul Hayati; Noratul Hafdhah; . Junaidi (Syiah Kuala University, 2013)
Pegagan (Centela asiatica [L] Urban) contains alkaloid, flavonoid, saponin, triterpenoid and tannin that have antibacterial activity. Staphylococcus aureus and Klebsiella pneumoniae are most common of bacteria that cause pneumonia. This study conducted t odetermine the effect of ethanol extracts of pegagan in inhibiting the growth of S. aureus and K. pneumoniae that caused pneumonia. The type of this study is a laboratory experiment using a completely randomized design (CRD). Testing of inhibitory growth effect was measured by Kirby Bauer disc diffusion method. The results showed that ethanol extracts of pegagan at 12.5%, 25%, 50% and 75% concentrations formed inhibition zones on the growth of S. aureus, on average respectively of 7.00 mm, 9.20 mm, 13.20 mm, and 14.50 mm, whereas on the growth of K. pneumoniae, it didn’t form any inhibition zone. The results of ANOVA and Duncan (α=1%) tests showed that ethanol extracts of pegagan at all concentrations made a significant difference in inhibiting the growth of S. aureus compared to negative and positive control. The ability of ethanol extracts of pegagan to inhibit the growth of S. aureus at 12.5% and 25% concentrations categorized as no inhibitory growth effect, whereas 50% and 75% concentrations categorized as weak inhibitory growth effect. While the ethanol extracts of pegagan at all concentrations of the tests categorized as no inhibitory growth effect for K. pneumoniae. It can be concluded that ethanol extracts of pegagan inhibit the growth of S. aureus, but do not inhibit the growth of K. pneumoniae.